Predicting EFL Teacher’s Perceived Self-Disclosure Practice: Demographic Factors in Focus - Masoud Taheri; Mohsen Shahrokhi; Mohammad Reza Talebinejad (Journal of Modern Research in English Language Studies, 2024)
Academics have generally accepted that teachers' interpersonal communication techniques and strategies—specifically, teachers' self-disclosure—are excellent instructional tools. The exploration of English as a Foreign Language (EFL) teachers' perceptions regarding their self-disclosure practice and its relationship with demographic factors, which can also significantly contribute to the variation of the teachers' self-disclosure in EFL contexts, has been largely neglected in the Iranian EFL context despite the growing body of research in this area. To close this gap, the present research distributed a five-point Likert scale to the participants to gather their perceptions on self-disclosure as Iranian EFL instructors. The inferential statistical analyses revealed a high extent of self-disclosure is practiced by Iranian EFL teachers. Moreover, Hierarchical Multiple regression indicated that among degree, experience, age, and gender as demographic factors, all, except gender, are associated with EFL teachers’ self-disclosure, and could predict teachers’ self-disclosure significantly. The study provides implications for stakeholders in the EFL community.